Generosity is a dangerous game: aid allocation and the risks of terrorism - Nemeth, Stephen C (Terrorism and political violence, 2020)
While evidence has suggested that international assistance projects become the targets of violence, political science research has often addressed this relationship at the state level and not the aid location itself. Given the heterogeneous nature of aid distribution and terrorist behavior within a state, it is important to study this relationship using higher resolution data. Using geocoded terrorist attack and multilateral aid distribution data, coupled with the PRIO-GRID cell structure, our approach sheds light on whether areas in which aid is distributed are more likely to be targeted by terrorist groups. Our results show that areas where aid is being distributed are targeted more heavily than areas without aid distribution. The modality of specific multilateral aid projects is also shown to impact whether they are more likely to be targeted. Further, we show that terrorists select different types of targets in aid locations than they do in non-aid locations, lending support to the notion that terrorists seek to intimidate local populations from collaboration with the government and to dissuade further government efforts. The results not only highlight and expand upon the dangers associated with aid distribution, but also the notion that aid content is a factor in terrorist targeting preferences.